Hydrogen Attenuates Endotoxin-Induced Lung Injury by Activating Thioredoxin 1 and Decreasing Tissue Factor Expression - Li, Qian; Hu, Liang; Li, Juan; Yu, Pan; Hu, Fan; Wan, Bing; Xu, Miaomiao; Cheng, Huixian; Yu, Wanyou; Jiang, Liping; Shi, Yadan; Li, Jincan; et al. (Frontiers in Immunology, 2021)
Septic lung injury is one of the major causes of death induced by sepsis, however, few effective therapeutic options exist. Hydrogen inhalation has recently been shown to be an effective treatment for inflammatory lung injury, but the underlying mechanism is unknown. In the current study we aim to investigate how hydrogen attenuates septic lung injury and provide reference values for the clinical application of hydrogen. LPS was used to establish a septic lung injury mouse model. The survival rate and pulmonary pathologic changes were evaluated. THP-1 and HUVECC cells were cultured in vitro. The thioredoxin 1 (Trx1) inhibitor was used to evaluate the anti-inflammatory effects of hydrogen. Hydrogen significantly improved the survival rate of mice, reduced pulmonary edema and hemorrhage, infiltration of neutrophils, and IL-6 secretion. Inhalation of hydrogen decreased tissue factor (TF) expression and MMP-9 activity, while Trx1 expression was increased in the lungs and blood of septic mice. LPS-stimulated THP-1 and HUVEC-C cells in vitro and showed that hydrogen decreases TF expression and MMP-9 activity, which were abolished by the Trx1 inhibitor, PX12. Hydrogen attenuates septic lung injury by decreasing TF expression and MMP-9 activity via activating Trx1. Targeting Trx1 by hydrogen may be a potential treatment for septic lung injury.